Community Peer-Led Falls Prevention Presentations: What Do the Experts Suggest? - Khong, L.; Berlach, R.; Hill, Keith; Hill, Anne-Marie (Springer, 2018)
© 2018 Springer Science+Business Media, LLC, part of Springer Nature Falls among older adults are a major problem. Despite considerable progress in falls prevention research, older adults often show low motivation to engage in recommended preventive strategies. Peer-led falls prevention education for older adults may have potential for bridging the research evidence-practice gap, thereby promoting the uptake of falls prevention strategies. We evaluated peer educators’ presentations of falls prevention education to community-dwelling older adults in regard to established criteria that were consistent with adult learning principles, the framework of health behaviour change, falls prevention guidelines, and recommendations for providing falls prevention information. We conducted a within-stage mixed model study using purposive and snowball sampling techniques to recruit 10 experts to evaluate video recordings of the delivery of three peer-led falls prevention presentations. Each expert viewed three videos and rated them using a questionnaire containing both open-ended and closed items. There was a good level of expert agreement across the questionnaire domains. Though the experts rated some aspects of the presentations highly, they thought that the presentations were mainly didactic in delivery, not consistently personally relevant to the older adult audience, and did not encourage older adults to engage in the preventive strategies that were presented. Based on the experts’ findings, we developed five key themes and recommendations for the effective delivery of peer-led falls prevention presentations. These included recommending that peer educators share falls prevention messages in a more interactive and experiential manner and that uptake of strategies should be facilitated by encouraging the older adults to develop a personalised action plan. Findings suggest that if peer-led falls prevention presentations capitalise on older adults’ capability, opportunity, and motivation, the older adults may be more receptive to take up falls prevention messages.